2021
DOI: 10.1155/2021/6646702
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyurethane/Pluronic F127 Nanofibers Containing Peppermint Extract Loaded Gelatin Nanoparticles for Diabetic Wounds Healing: Characterization, In Vitro, and In Vivo Studies

Abstract: Diabetic ulcer is regarded as one of the most prevalent chronic diseases. The healing of these ulcers enhances with the use of herbal extracts containing wound dressings with high antibacterial property and creating a nano-sized controlled release system. In this study, new peppermint extract was incorporated in the polyurethane- (PU-) based nanofibers for diabetic wound healing. The peppermint extract was used as an herbal antimicrobial and anti-inflammatory agent. The absorption ability of the wound dressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…The wound dressing comprising 15% natural Malva extract presented the wound healing rapidity of 95.05 ± 0.24% by day 14. Additionally, from the histological images, it was noted that macrophage infiltration, neovascularization activity, and fibroblastic proliferation increased on the 7th day and the grade of collagenization and epithelium regeneration was increased on the 14th day [51,52].…”
Section: Polyurethanes Modified With Antimicrobial Compoundsmentioning
confidence: 99%
“…The wound dressing comprising 15% natural Malva extract presented the wound healing rapidity of 95.05 ± 0.24% by day 14. Additionally, from the histological images, it was noted that macrophage infiltration, neovascularization activity, and fibroblastic proliferation increased on the 7th day and the grade of collagenization and epithelium regeneration was increased on the 14th day [51,52].…”
Section: Polyurethanes Modified With Antimicrobial Compoundsmentioning
confidence: 99%
“…Among them, anti-inflammatory electrospun nanofibers play vital roles in the regeneration of skin [17,18], bone [19,20], blood vessel [21,22], and nerve [23,24] due to the nano-size architecture similar to the extracellular matrix [25] capable of delivering many types of drugs and bioactive materials [26]. For example, polyurethane/pluronic F127 nanofibers containing peppermint extract (an anti-inflammatory agent)-loaded-gelatin nanoparticles were prepared to promote diabetic wound healing [27]. Similarly, Lawsonia inermis was used as an anti-inflammatory agent and added to the gelatin-oxidized starch to generate nanofibers through electrospinning [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive constituents such as phenolic compounds, saponins, tannins, quinones, and flavonoids typically found in plants have been used for the fabrication of functional fibers. It is reported that different plants are rich in phenolic compounds, and they have been incorporated into fiber production [40][41][42][43]. For instance, Hani et al [44] coupled Moringa oleifera leaf crude ethanolic extract rich in quercetin, kaempferol, and ascorbic acid with GL to generate nanofibers via an E-spinning method that could act as a potential oxidative stress inhibitor.…”
Section: Introductionmentioning
confidence: 99%